Evaluating soil quality status of fluvisols at the regional scale. A multidisciplinary approach crossing multiple variables - Rodrigo-Comino, Jesús; Keshavarzi, Ali; Senciales-González, José María (Wiley, 2021)
Rivers condition natural and human ecosystems, providing fertile soils and water for irrigation and consumption in rural and urban uses. However, the intensification of human activities and inherent environmental conditions (e.g., topography, slope or climate) are changing the sustainability of fluvial soil ecosystems. This is problematic, especially in the Mediterranean belt, because of a lack of studies at the regional scale that evaluates soils traditionally associated with rivers such as the “Fluvisols” (IUSS-WRB). Therefore, the main aim of this paper is to understand the current status of fluvial soils in the Málaga province (Southern Spain) within the Mediterranean belt considering: (1) different thematic maps; (2) soil profiles; and (3) a soil quality index. Fluvisols of the region were assessed using fieldwork, extensive soil data sources and soil profiles including specific information on soil physicochemical properties and crossing environmental conditions. A total of 195.22 km2 of fluvisols can be found in Málaga. About 42.5% of the fluvisols are used for human activities such as agriculture (rainfed and irrigation fields, or woody crops such as olives or vineyards), mining, industries and services, urban areas or reservoirs. More than 58% of the fluvisols are located in the warmest territories registering the highest evapotranspiration rates and lowest rainfall amount. The soil quality index reaches lower scores for the fluvisols having mean values of 0.58 (1 = maximum possible score). We conclude that the characterization from a regional scale shed light on the current status of the fluvisols and possible responses against human impacts and river evolution dynamics.
Keywords: Suelos - Calidad; Fluvisuelos - Málaga; Fluvial ecosystems; Human activities; Mediterranean; Soil quality index; Soils; Regional geography